2003
DOI: 10.1590/s0103-90162003000200028
|View full text |Cite
|
Sign up to set email alerts
|

Digital-image analysis to predict weight and yields of boneless subprimal beef cuts

Abstract: For several decades, beef carcass evaluation for grading or research purposes has relied upon subjective visual scores, and manually taken measurements, but in recent times there has been a growing interest in new technologies capable of improving accuracy of estimates. Equations to predict weight and yield of beef pistol subprimal cuts were developed in this work using digital image analysis (VIA) of the 12 th rib steak. Equations to predict total pistol subprimal cuts weight (CUTS) had coefficients of determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…These findings are summarised in Table 3. The R 2 and RSD values were very low in the results presented by Teira et al (2003), which is probably because there was very little variation (CV = 4.0%) in SMY% in the Nelore steers used in that experiment. In contrast, a higher amount of variation (CV = 9.6%) existed between steers and heifers in the results of Shackelford et al (1998) and a higher R 2 and lower RSD values for the prediction equation were obtained.…”
Section: Refinement Of Viamentioning
confidence: 71%
See 2 more Smart Citations
“…These findings are summarised in Table 3. The R 2 and RSD values were very low in the results presented by Teira et al (2003), which is probably because there was very little variation (CV = 4.0%) in SMY% in the Nelore steers used in that experiment. In contrast, a higher amount of variation (CV = 9.6%) existed between steers and heifers in the results of Shackelford et al (1998) and a higher R 2 and lower RSD values for the prediction equation were obtained.…”
Section: Refinement Of Viamentioning
confidence: 71%
“…A different approach to collect VIA data that involved removing a section of M. longissimus thoracis from the posterior half of the 12th thoracic vertebra has been tried a number of times with varying results (Farrow, Loneragan, Pauli, & Lawrence, 2009;Shackelford, Wheeler, & Koohmaraie, 1998;Teira, Tinois, Lotufo, & Felício, 2003). Shackelford et al (1998) developed a 5 variable prediction equation, that accounted for 89% of the variation in SMY% across the combined experimental and validation datasets.…”
Section: Refinement Of Viamentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, computer-aided software has been developed and this software has been used for livestock production. Investigations have shown that the digital image analysis has been applied to determine meat quality, egg quality, marbling score, BM, liveweight and growth of pigs, rabbits, chickens, horses, goats, sheep and cattle (McDonald and Chen 1990;Kuchida et al 1991;Shackelford et al 1998;Shiranita et al 1998;Karnuah et al 2001;Cannell et al 2002;Teira et al 2003;De Wet et al 2003;Aktan 2004;Bozkurt et al 2007;Negretti et al , 2008Negretti et al , 2011Ozkaya and Bozkurt 2008;Wang et al 2008;Mollah et al 2010;Tasdemir et al 2011). Stajnko et al (2008) reported that the BM and liveweight of the bulls were estimated by thermal camera.…”
Section: Introductionmentioning
confidence: 99%
“…LI et al, (1997) showed that brittleness of meat could be determined by vision texture analysis. Similarly, investigations have shown this method can be used to analyze meat, determine marbling score and evaluate MLD area (NEWMAN, 1984;KUCHIDA et al, 1991;SHACKELFORD et al, 1998;SHIRANITA et al, 2000;KARNUAH et al, 2001;CANNELL et al, 2002;TEIRA et al, 2003). BOZKURT et al, (2006) used digital image analysis technology regarding prediction of body weight from body measurements in beef cattle.…”
Section: Introductionmentioning
confidence: 99%